Development of flexible automation for the car seat polyurethane injection molding line / Ahmed Jaffar and Noriah Yusoff - Yusoff, Noriah; Jaffar, Ahmed (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
Car seat polyurethane injection and molding process is a method of producing car seats to meet customer satisfaction such as car styling and comfort as well as its ergonomic functions. An on-site study was carried out at a local Small and Medium Enterprise company which located in Klang Valley, Selangor. An investigation on the existing car seat polyurethane injection process was conducted at the case study subject and the processing time data was gathered for the establishment of the important simulation modeling parameters or the benchmark key parameters. A conceptual new improved method was then developed, tested and validated for its workability and performance using QUEST discrete event simulation software. There are two major phases involved in this research work; (i) analysis and development of an improved method using work study method and (ii) modeling and simulation of that improved method using Delmia QUEST Simulation Software (DQSS). An investment analysis was done to compare the economics of the new improved method against the present method, using the payback period and the return on investment formulae. A prototype model was also developed to show the mockup of the suggested system. This prototype model can be integrated with other features such as robot's manipulator and transfer lines to form an automated production line.